DESIGN OF SOLAR PHOTOVOLTAIC MICRO-POWER SUPPLY FOR APPLICATION OF WIRELESS SENSOR NODES IN SIMPLE ILLUMINATION ENVIRONMENTS. - Abir Kessebi, Pr.Bahri Rezig (International Journal of Research Science and Management, 2018)
Nowadays, it can be observed that Wireless Sensors Networks (WSN) are taking increasingly vital roles in many applications. However, the main challenging issue with adopting WSN technology is the use of power sources such as batteries and supercapacitors, which have a limited lifetime. A smart solution that could tackle this problem is using ambient Energy Harvesting technology. This paper presents a WSN microsystem with indoor light power harvesting using photovoltaic (PV) cell. The indoor light is a remix of artificial and natural light simulated in an office in Tunisia. We have evaluated the amount of light, his availability and the power that the PV cell can provide to the WSN. The WSN average energy consumption was calculated using the Heinzelman model. Simulation studies confirm that a 30 cm2 PV cell can satisfy the need of a low duty cycle sensor Node. Finally we propose a power management design through harvesting hybrid indoor light. The approach is inspired by the use of the Fractional Open Circuit Voltage based Maximum Power Point tracking (MPPT) concept for sub mw PV cells. Three scenarios of boost converter (BC) were studied in this work, first scenario is a typical BC with an input capacitor, second scenario is a BC without an input capacitor, and third scenario is a direct connection. We focused on analyzing the state of charge (SoC) of the output capacitor in those three scenarios and also when varying the number of series connected PVcells. At conclusion the validated scenario is the one who gives a better stabilization of PV cell voltage around the MPP and a better SoC for the energy storage unit.